Analysis of Grammatical Cohesion in The Russia-Ukraine War News Text - Sahreebanu, Dhea Syahzana (English Literature Study Program, 2023)
Grammatical cohesion is research that analyzes how each word, phrase, or sentence is connected in a text. The researcher conducted this study to identify the types of grammatical cohesion and know how these types work in news texts. Researchers chose to use a qualitative descriptive approach in conducting this research. The data source in this study is an online news text published on Wednesday, 19 October 2022, by The Jakarta Post entitled